Needs Analysis for Developing AI-Based E-Modules to Improve Students Digital Literacy in History at SMA Muhammadiyah 1 Palembang - Muhamamd Fadlurrohman Shubhi; Syarifuddin Syarifuddin (UIN Fatmawati Sukarno Bengkulu, 2025)
The development of digital technology demands a transformation in the world of education, including the development of learning media that is innovative and adaptive to the needs of students. This study aims to analyze the needs of students in the development of E-Modules based on Artificial Intelligence (AI) in history subjects at SMA Muhammadiyah 1 Palembang. The method used was a mixed qualitative and quantitative approach with a survey design. Data was collected through distributing questionnaires to students and analyzed descriptively. The results showed that 85.4% of learners were interested in the application of AI in learning, 80.6% were interested in using the E-Module, and 62.9% had previous experience in using it. In addition, 51.6% of learners have a visual learning style, while the lecture method still dominates history learning by 30.6%. These findings suggest that the development of AI-based E-Modules is needed to overcome the limitations of conventional learning methods and support the improvement of digital literacy, learning engagement, and 21st century competencies.